ORGANIZATION OF POSTGRADUATE TRAINING OF CIRCULAR ECONOMY SPECIALISTS IN THE REPUBLIC OF POLAND (ON THE EXAMPLE OF SILESIAN POLYTECHNICS) - Oleksii Sysoiev (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article is devoted to the analysis of the organization and content of postgraduate training of specialists in circular economics in the Republic of Poland on the example of Silesian Polytechnic. It is emphasized that the Republic of Poland is taking significant steps in the development of the circular economy and the training of specialists to implement its ideas. Based on the analysis of postgraduate education programs «Circular Economics and Cleaner Production in Practice» and «Cyclic Engineering» in the Silesian Polytechnic, the article reveals the requirements the requirements, rights and responsibilities of postgraduate students are revealed; knowledge, skills and competencies that they acquire in the process of training in circular economics programs; forms of education and the content of diplomas that students receive after training, as well as areas of possible employment. It is emphasized that in the system of postgraduate education of Silesian Polytechnic there are programs both directly from the circular economy and from certain problems that relate to the scope of such specialists and contribute to the development of a circular economy. It is proved that the training of specialists in circular economics in postgraduate studies acquires a systemic character in terms of coverage of the content of those problems that relate to the professional activities of specialists in circular economics. The indisputable value of such educational programs is to involve in their development and determine the content of training not only teachers of higher education institutions, but also public and professional societies that care for the environment, waste recycling and more. Educational programs on circular economics at Silesian Polytechnic are practice-oriented, they include consultations in circular production companies, trainings on business practice, as well as the development of an implementation project under the guidance of experts.